2013
DOI: 10.1001/jama.2013.1954
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aliskiren on Postdischarge Mortality and Heart Failure Readmissions Among Patients Hospitalized for Heart Failure

Abstract: NHIBITION OF THE RENIN-ANGIOTENsin-aldosterone system (RAAS) has long been recognized as a lifeprolonging therapy for patients with chronic heart failure (HF) with reduced left ventricular ejection fraction (LVEF), 1 and angiotensinconverting enzyme (ACE) inhibitors, angiotensin II receptor blockers (ARBs), and mineralocorticoid receptor antagonists (MRAs) are recommended by all major national guidelines. 2,3 However, although the benefits of these treatments are undisputed, these agents induce a compensatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
220
2
18

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 316 publications
(245 citation statements)
references
References 30 publications
5
220
2
18
Order By: Relevance
“…40 However, therapeutic combination of aliskiren with either an ACE inhibitor or an ARB results in a greater frequency of adverse events, fails to improve left ventricular remodeling after myocardial infarction, fails to reduce cardiovascular and renal events in high-risk patients with type 2 diabetes mellitus, and fails to reduce postdischarge mortality and heart failure readmissions in hospitalized patients with heart failure. [41][42][43] Similar increases in adverse effects were observed with combinations of ACE inhibitors and ARBs. 44,45 The adverse effects associated with combinations of renin-angiotensin system inhibitors are likely due to excessive blockade of AT 1 receptor-mediated effects.…”
Section: Discussionmentioning
confidence: 66%
“…40 However, therapeutic combination of aliskiren with either an ACE inhibitor or an ARB results in a greater frequency of adverse events, fails to improve left ventricular remodeling after myocardial infarction, fails to reduce cardiovascular and renal events in high-risk patients with type 2 diabetes mellitus, and fails to reduce postdischarge mortality and heart failure readmissions in hospitalized patients with heart failure. [41][42][43] Similar increases in adverse effects were observed with combinations of ACE inhibitors and ARBs. 44,45 The adverse effects associated with combinations of renin-angiotensin system inhibitors are likely due to excessive blockade of AT 1 receptor-mediated effects.…”
Section: Discussionmentioning
confidence: 66%
“…It was initially suggested that a combined treatment with aliskiren and an ACE inhibitor, or an angiotensin receptor blocker, could offer major benefits in patients with elevated cardiovascular risk. However, recently, concerns have raised about the clinical use of aliskiren in patients with NIDDM, especially when associated with ACE inhibitors, by the results of at least a couple of studies, 44,45 suggesting that the addition of aliskiren to standard therapy with renin-angiotensin system blockers might be even harmful. 44 Also in nondiabetic patients, there are concerns about the association of aliskiren with ACE inhibitors or angiotensin receptor blockers.…”
Section: Discussionmentioning
confidence: 99%
“…Among patients hospitalized for worsening chronic heart failure with reduced left ventricular ejection fraction, adding aliskiren (150-300 mg/day) to standard therapy did not reduce cardiovascular death or heart failure rehospitalization at 6 months or 12 months after discharge. Moreover, the rates of hyperkalaemia, hypotension, and renal impairment/ renal failure were higher in the aliskiren group compared with placebo [43]. According to the European Society of Cardiology -Heart Failure Association, aliskiren is not presently recommended as an alternative to an ACE inhibitor or ARB in patients with heart failure [44].…”
Section: Pharmacology Of Aliskirenmentioning
confidence: 99%